Pengembangan koleksi Perpustakaan Samudra Pustaka Desa Plosorejo Kecamatan Kademangan Kabupaten Blitar - Nurman Widodo; Moch Syahri (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. This study aims to describe the collection development of the Samudra Pustaka Library.. Samudra Pustaka Library is a village library that became the best village library in 2021 nationally. The completeness of the collection is one of the indicators of the success of managing the village library management. Data Collection Methods. The method used was a qualitative descriptive with several data collection techniques including interviews, observations, and documentation studies. Data Analysis. Data analysis was conducted by following stages of collection development developed by Evans and Saponaro Results and Discussion. Samudra Pustaka Library currently does not have their own collection development policy Societal analysis was conducted based on user suggestions and identified community livelihoods.. Selection criteria focus on purchases, donations, and collaboration. Weeding activities are carried out by withdrawing collections deemed unreadable. Evaluation activities are carried out by taking into account user suggestions related to collections. Several identified constraints were found on the budget, collections, and human resources. Conclusion. All collection development processes are on the right track. A collection development policy should be created immediately.